2002
DOI: 10.1159/000057669
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan (CPT-11) in Patients with Advanced Colon Carcinoma Relapsing after 5-Fluorouracil-Leucovorin Combination

Abstract: The purpose of the present study was to investigate the association between performance status (PS) and mean dose of irinotecan (CPT-11) in patients with recurrent advanced colorectal cancer relapsing after 5-fluorouracil and leucovorin chemotherapy. Patients who had completed their last chemotherapy course with 5-fluorouracil and leucovorin for at least 6 weeks and progressed were included. Based on PS, we administered a starting dose of 250 mg/m2 in patients with a PS 70–80 (group A), and 350 mg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…5-FU is a fluoropyrimidine that demonstrated a dual mechanism of action: brief exposure to 5-FU induced an RNA-directed toxicity, while TS inhibition and DNAdirected toxicity occurred with prolonged exposure [7,8]. CPT-11 (7-ethyl-10-[4-(1-piperidino)-1-piperidino] carbonyloxy-camptothecin; irinotecan; Camptosar ® ) is a topoisomerase-I-inhibiting agent that has shown antitumor activity in patients with colon cancer when administered alone as first-line therapy or as second-line therapy after 5-FU failure [9,10]. CPT-11 is enzymatically converted by carboxylesterases to its most active metabolite, SN-38 (7-ethyl-10-hydroxyl-camptothecin) [11].…”
Section: Introductionmentioning
confidence: 99%
“…5-FU is a fluoropyrimidine that demonstrated a dual mechanism of action: brief exposure to 5-FU induced an RNA-directed toxicity, while TS inhibition and DNAdirected toxicity occurred with prolonged exposure [7,8]. CPT-11 (7-ethyl-10-[4-(1-piperidino)-1-piperidino] carbonyloxy-camptothecin; irinotecan; Camptosar ® ) is a topoisomerase-I-inhibiting agent that has shown antitumor activity in patients with colon cancer when administered alone as first-line therapy or as second-line therapy after 5-FU failure [9,10]. CPT-11 is enzymatically converted by carboxylesterases to its most active metabolite, SN-38 (7-ethyl-10-hydroxyl-camptothecin) [11].…”
Section: Introductionmentioning
confidence: 99%
“…irinotecan, it is the limiting toxicity [1] . Any part of the gastrointestinal tract may be affected.…”
mentioning
confidence: 99%
“…However, these protocols carry some degree of morbidity with moderate side effects relating especially to L-OHP as grade 3/4 neutropenia or neurotoxicity occurring in 41.7 and 68% of the patients, respectively [19,21] . The high reported response rate mentioned above was very disappointing when treating patients who were refractory to 5FU/folinic acid and irinotecan amounting to between 15 and 25% [22,23] . Our trial demonstrated a 40% partial response rate and stable disease for at least 4 months in 13% of the patients.…”
Section: Discussionmentioning
confidence: 99%